Implementation of Energy Efficiency Improvement Measures in Romania and the Role of Professional Accountants - Daniela Artemisa Calu; Adriana Ana Maria Davidescu; Alina Mihaela Irimescu; Corina-Graziella Bâtcă Dumitru; Viorel Avram (Amfiteatru Economic)
Energy efficiency is one of the main objectives of the European Union's policy. Organisations are trying to implement various measures to improve energy efficiency to optimise their business models. Professional accountants prepare the financial and nonfinancial information of the organisations. In this context, the objectives of the document are: (i) to assess progress in the implementation of energy efficiency improvement measures (EEIMs) within some Romanian organisations and (ii) to assess the usefulness of energy efficiency improvement measures and the perceived impact of these measures on the organisation. In this regard, exploratory research was carried out based on a questionnaire to which 445 professional accountants from Romania responded. The research results indicate that the most frequently implemented measure to increase energy efficiency for organisations in Romania is the purchase of equipment/computers with a lower energy consumption. Furthermore, there are differences in the implementation of each measure, depending on the size of the organisation and the activity sector. The implementation of all energy efficiency improvement measures, evaluated based on an original composite indicator, is achieved at an average level, and it is more frequent in the trade sector (except the construction products sector), services sector (except the architecture sector, consultancy in construction, engineering) and manufacturing sector, as well as in micro, medium, and large entities. Furthermore, professional accountants believe that the most useful measure of improving energy efficiency that an organisation could implement is the use of assets that belong to the highest class of energy efficiency. Our research helps identify the most practical measures that the state can adopt and that organisations can implement to improve energy efficiency